Healing the Rift between Theology and Spirituality: Theological Commentary on Chatlos's Framework of Spirituality - Watts, Fraser N. (Zygon, 2025)
There is often an unnecessary relationship of mistrust between theology and advocates of spirituality. Theological misgivings about a spirituality that is independent of religion focus largely on concerns about what the word spiritual means; questions about how spirituality relates to religion; concerns about an overemphasis on subjective experience in the framework of spirituality (FOS); the question of whether there are external influences on religious and spiritual experience; and the prospects for interdisciplinary work on spirituality between theology, science, and philosophy. I suggest that the FOS is less nonreligious, as often assumed, but rather stands in a distinct quasi-religious tradition, and that internal and external influences on spiritual experience should not be regarded as alternatives. My hope is that there will be more fruitful dialogue between theology and the FOS, though that depends on a better understanding of the nature of the various disciplines involved and respect for their various core assumptions.